(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pandanus Roxb. a medicinally important plant belongs to the Family Pandanaceae. It is an important leafy vegetable and the leaves are widely used in Indian cookery for flavouring foodstuffs. Green leafy vegetables are a blessing for a safe and healthier life and have been in use for centuries. It provides vital nutrients require for human health and wellbeing. Since ancient times, green leafy vegetables have been used as medicine and have a great impact of our diet and nutrition. Gas chromatography-mass spectroscopy (GC-MS) is a tool capable of identifying active principles in plant’s extractions. Plants are the natural source of bioactive components responsible for the medicinal efficacy due to the presence of by product. 81 compounds were detected in ethanol extract of Pandanus amaryllifolius. Squalene was identified as the major compound.